1992
DOI: 10.1007/bf02245485
|View full text |Cite
|
Sign up to set email alerts
|

Oral ethanol self-administration in rats is reduced by the administration of dopamine and glutamate receptor antagonists into the nucleus accumbens

Abstract: The purpose of this study was to assess the role of endogenous dopamine and glutamate systems within the nucleus accumbens in modulating responses for oral ethanol reinforcements (10% w/v) in a free-choice operant task. Pretreatment with both systemic (100 micrograms/kg) and intra-nucleus accumbens microinjection of fluphenazine (2 and 4 micrograms), a dopamine receptor antagonist, significantly decreased responding for ethanol, without significantly affecting responses for water. Ethanol self-administration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(152 citation statements)
references
References 49 publications
12
138
2
Order By: Relevance
“…Since there are DA-independent outputs of the VTA that can contribute to behavioral reinforcement (Nader and van der Kooy, 1997;Laviolette et al, 2004), it is possible that projecting glutamate or GABA VTA neurons are responsible for the modulation of drinking reported here. DA may also be involved in this modulation, since DA agonists and antagonists alter drinking (Pfeffer and Samson, 1988;Weiss et al, 1990;Rassnick et al, 1992Rassnick et al, , 1993Cohen et al, 1998Cohen et al, , 1999. If DA does play a role in DOR-mediated EtOH consumption, our data are consistent with an inverted u-shaped relationship between DA level and reward value.…”
Section: Discussionsupporting
confidence: 77%
“…Since there are DA-independent outputs of the VTA that can contribute to behavioral reinforcement (Nader and van der Kooy, 1997;Laviolette et al, 2004), it is possible that projecting glutamate or GABA VTA neurons are responsible for the modulation of drinking reported here. DA may also be involved in this modulation, since DA agonists and antagonists alter drinking (Pfeffer and Samson, 1988;Weiss et al, 1990;Rassnick et al, 1992Rassnick et al, , 1993Cohen et al, 1998Cohen et al, , 1999. If DA does play a role in DOR-mediated EtOH consumption, our data are consistent with an inverted u-shaped relationship between DA level and reward value.…”
Section: Discussionsupporting
confidence: 77%
“…Although the neurobiological systems that regulate ethanol self-administration remain to be fully characterized, it is widely accepted that the nucleus accumbens plays a role in this behavior (e.g., Hodge et al, 1995Hodge et al, , 1992Rassnick et al, 1992;Weiss et al, 1993). We previously showed that PKCε null mice self-administer less ethanol than wild-type controls and show no increase in dopamine levels in the nucleus accumbens after acute ethanol treatment (Olive et al, 2000), suggesting that PKC modulation of dopamine in this brain region may regulate ethanol self-administration.…”
Section: Discussionmentioning
confidence: 99%
“…One important consideration is that Famous et al (2007) used a higher dose of AP5 (3 and 30 mg) to promote reinstated cocaine seeking, whereas Bäckström and Hyytiä (2007) found that lower doses of AP5 (1 and 2 mg) inhibit cue-induced cocaine seeking. Infusion of AP5 into the accumbens (no distinction made between the NAcore and NAshell) also decreases the potentiation of conditioned reinforcement caused by D-amphetamine (Burns et al, 1993) and decreases oral ethanol self-administration (Rassnick et al, 1992).…”
Section: B N-methyl-d-aspartate Receptorsmentioning
confidence: 99%